2018
DOI: 10.1016/j.fm.2017.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Internalization and dissemination of human norovirus and Tulane virus in fresh produce is plant dependent

Abstract: Human norovirus (NoV) is a leading cause of fresh produce associated outbreaks. Previous research indicates that the roots of growing leafy greens and berries internalize human NoV. However the effect of plant type and inoculum level on internalization rates has not been directly compared. In this study we compared the internalization and dissemination rates of human NoV and its surrogate, Tulane virus (TV) in green onion, radishes, and Romaine lettuce. We also evaluated the effect inoculum level and plant gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
1
12
0
2
Order By: Relevance
“…Norovirus is the leading cause of food borne illness accounting for 45% of illnesses in produce (Gould et al, 2013). Numerous studies have established that human norovirus is able to attach and internalize in a variety of row vegetable crops (Hirneisen and Kniel, 2013;DiCaprio et al, 2015a,b;Markland et al, 2017;Yang et al, 2018). These studies suggest the multiple routes in which NoV can internalize and transport to various tissues of the plant and the potential immune response of plants to these pathogens.…”
Section: Food Safety In the Twenty First Century: The Need For A New mentioning
confidence: 99%
“…Norovirus is the leading cause of food borne illness accounting for 45% of illnesses in produce (Gould et al, 2013). Numerous studies have established that human norovirus is able to attach and internalize in a variety of row vegetable crops (Hirneisen and Kniel, 2013;DiCaprio et al, 2015a,b;Markland et al, 2017;Yang et al, 2018). These studies suggest the multiple routes in which NoV can internalize and transport to various tissues of the plant and the potential immune response of plants to these pathogens.…”
Section: Food Safety In the Twenty First Century: The Need For A New mentioning
confidence: 99%
“…Metagenomic analysis of romaine and iceberg lettuce has shown the presence of wide range of plant and animal/ human viruses already on the field [63•]. It has also been shown that NoV can be internalised by some plants such as lettuce and strawberries through the root system and can therefore be present inside the plant and fruits rather than just contaminating the surface [64,65]; similar to the internalisation and retention of acid resistant viruses in water filtering molluscs [66]. Even though being internalised, NoV, such as most animal and human viruses, is not able to infect or replicate in plant cells [67].…”
Section: Other Food-contaminating Virusesmentioning
confidence: 99%
“…In the same study, the surrogate virus canine calicivirus (CaCV) did not mimic HuNoV behavior and was shown to be internalized infrequently through the roots into the leaves of lettuce seedlings (26). In contrast, another laboratory reported the internalization of HuNoV through the roots into the leaves of lettuce seedlings (3 weeks of age) and in 2-month-old green onions (24,25). The authors maintained their plants under laboratory conditions of 40% relative humidity, which may have enhanced the passive internalization of the virus, driven by increased transpiration rate of the plants under low relative humidity, as was shown for MNV in lettuce (39).…”
Section: Discussionmentioning
confidence: 99%
“…Internalization may also depend on the virus and the plant type, as TV at a low inoculum (10 4 GE/ml in 400 ml, i.e., 4 ϫ 10 6 GE/plant) or a high inoculum (10 6 GE/ml in 400 ml, i.e., 4 ϫ 10 8 in total feed water) was not detected in the leaves of green onions despite being detected in their roots (24). Furthermore, although washing the roots during the experimental setup may have caused minimal root damage and enhanced virus uptake, internalization of viruses in our study was not solely based on passive root uptake, as was evidenced by the different patterns of internalization for HuNoV and its surrogates SaV and TV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation